The Leadership Contract - Molinaro, Vince (Ascent Audio, 2019)
Step up, get tough, and commit to your decision to lead The Leadership Contract provides the manual that leaders around the world need. With only seven percent of employees feeling confident in senior leadership, the problem is evident: disappointing, and often disgraceful leaders. Employees deserve better than that; organizations need better than that-and this book provides a robust framework for stepping up and making the decision to lead. This new third edition has been updated, featuring a new foreword by Adecco CEO Alain Dehaze, new findings from the Global Leadership Accountability Study, and more insights to help you chart your own path to build strong leadership accountability at a personal and organizational level. Great leadership doesn't happen by accident. It's more than just being in charge; it's a decision, an obligation, and potentially your legacy. Mediocre is no longer good enough-in today's business climate, organizations need stellar leadership. If you're not exceptional, step up or step aside-this book helps you toughen up and put your commitment to great leadership in writing for yourself as much as everyone else.